2022
DOI: 10.1620/tjem.2022.j082
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Fertility in Women with Cesarean Scar Syndrome Is Associated with Chronic Inflammation in the Uterine Cavity

Abstract: Decreased fertility in women with cesarean scar syndrome is associated with chronic inflammation in the uterine cavity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Gulz et al 49 showed that endometriosis was diagnosed during laparoscopic surgery in 22 of 83 patients (27%). In contrast, our recent report demonstrated that endometriosis was detected in 51 (70%) patients with CSDi, although majority of patients were not at a severe stage of endometriosis 62 . Of these patients with endometriosis, 85% had only peritoneal lesions.…”
Section: Decreased Fertility In Women With Csdimentioning
confidence: 63%
See 1 more Smart Citation
“…Gulz et al 49 showed that endometriosis was diagnosed during laparoscopic surgery in 22 of 83 patients (27%). In contrast, our recent report demonstrated that endometriosis was detected in 51 (70%) patients with CSDi, although majority of patients were not at a severe stage of endometriosis 62 . Of these patients with endometriosis, 85% had only peritoneal lesions.…”
Section: Decreased Fertility In Women With Csdimentioning
confidence: 63%
“…Microorganisms may be present because of the retention of blood in CSD and contribute to chronic inflammation. Our group demonstrated that the frequency of chronic endometritis in women with CSDi was significantly higher than that in the general infertile population 62 . Additionally, we showed that higher levels of inflammatory cytokines (tumor necrosis factor‐a and interleukin‐1b) in women with CSDi were detected in the uterine cavity compared to women with a history of CS but without symptoms of CSDi.…”
Section: Decreased Fertility In Women With Csdimentioning
confidence: 65%
“…In recent years, the relationship between cesarean scar uterus and subsequent secondary infertility has been gradually recognized, but the specific mechanism is not clear [ 20 , 21 ]. Nobuta et al found that a cause of secondary infertility in women with cesarean scar syndrome may be chronic inflammation of the uterine cavity [ 22 ]. We also found that prior induced abortion, mode of termination of the last pregnancy, age at menarche, menstrual cycle, and level of dysmenorrhea had no effect on subsequent pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Various disorders, including endometrial polyps, intrauterine adhesions, hydrosalpinx, and cesarean scar defects, have been associated with incidence of CE. 27 , 28 , 29 , 30 CE cases with intrauterine abnormalities or a hydrosalpinx are usually treated through surgery without antibiotics. 27 , 28 , 29 In addition, systemic antibiotic treatment for CE with endometrial polyps may decrease clinical pregnancy rates during infertility treatment after surgery.…”
Section: Tests and Treatments For Implantation Failurementioning
confidence: 99%